2020
DOI: 10.7150/jbji.42448
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Versus Colistin in the Treatment of Carbapenem-resistant Acinetobacter baumannii Complex Osteomyelitis

Abstract: Abstract. Background: Acinetobacter baumannii complex is an increasingly important cause of osteomyelitis. It is considered a difficult to treat agent, due to increasing antimicrobial resistance and few available therapeutic options.Objective: To compare effectiveness and tolerability of tigecycline and colistin in patients with osteomyelitis caused by carbapenem-resistant A. baumannii complex (CRABC).Methods: This retrospective review included all patients admitted to a 150-bed tertiary hospital from 2007 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In contrast, for the in-hospital mortality, reported in six studies [ 12 , 15 , 16 , 17 , 19 , 23 ], no statistically significant advantage was reported with either monotherapy (OR = 1.42, 95% CI [0.55, 3.70], p = 0.47), Figure 5 , with a significant heterogeneity observed (I 2 = 51%, p = 0.07). However, when reversing the heterogeneity via the sensitivity analysis, by excluding the study by Ku et al [ 15 ], a statistically reduced in-hospital mortality rate was observed in favour of the colistin monotherapy (OR = 2.27, 95% CI [1.24, 4.16], p = 0.008), with no heterogeneity (I 2 = 0%, p = 0.57), Figure S1.2 .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In contrast, for the in-hospital mortality, reported in six studies [ 12 , 15 , 16 , 17 , 19 , 23 ], no statistically significant advantage was reported with either monotherapy (OR = 1.42, 95% CI [0.55, 3.70], p = 0.47), Figure 5 , with a significant heterogeneity observed (I 2 = 51%, p = 0.07). However, when reversing the heterogeneity via the sensitivity analysis, by excluding the study by Ku et al [ 15 ], a statistically reduced in-hospital mortality rate was observed in favour of the colistin monotherapy (OR = 2.27, 95% CI [1.24, 4.16], p = 0.008), with no heterogeneity (I 2 = 0%, p = 0.57), Figure S1.2 .…”
Section: Resultsmentioning
confidence: 91%
“…Fourteen studies [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] involving 1163 patients were included in the current study. A total of 789 patients were treated with tigecycline and 938 patients were treated with colistin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, clinical success was 75.0% in bone/joint infections caused by CRAB, which is higher than reported previously (approx. 40%) [16]. A common resistance mechanism in CRAB is the production of betalactamases (e.g., Class D, OXA-type), which do not affect the in vitro activity of OMC; therefore, OMC may represent a viable option in these clinical isolates, if proven efficacious [17].…”
Section: Discussionmentioning
confidence: 99%